ANALISIS PENGELOLAAN KEUANGAN PADA PERUSAHAAN WRP (WIRAUSAHA RAKYAT PERIKANAN) - Rivat, Rivat; Turi, La Ode; Syahrir, Sasmita Nabila (Komunitas Manajemen Kompetitif, 2025)
Effective financial management is the key to success for fisheries companies, including WRP (Wirausaha Rakyat Perikanan) located in Boepinang Barat Village. This study aims to analyze the financial management implemented by WRP companies, focusing on four main aspects: Budget planning, recording, reporting, and control. The research method used is a qualitative approach, which involves data collection through interviews and observations. The results of the study indicate that WRP companies face various challenges in financial management, including poor budget planning, incomplete transaction recording, and weak financial control. Fluctuations in fish prices influenced by market demand also have a significant impact on the company's financial performance. This study is expected to provide guidance and recommendations for WRP companies and other fisheries companies in improving their financial management, so that companies can achieve more optimal and sustainable business goals, and contribute positively to the regional economy. Keywords: Financial management, Wirausaha Rakyat Perikanan, Budget planning, recording, reporting, control.